Capital, State, Empire The New American Way of Digital Warfare - Timcke, Scott (Critical Digital and Social Media Studies, 2018)
The United States presents the greatest source of global geo-political violence and instability. Guided by the radical political economy tradition, this book offers an analysis of the USA's historical impulse to weaponize communication technologies. Scott Timcke explores the foundations of this impulse, then demonstrates how the militarization of digital society creates structural injustices and social inequalities. He analyses how new digital communication technologies support and fund indirect and informal means that ensures American paramountcy, in turn sustaining enduring conditions for worldwide capital accumulation. Identifying selected features of contemporary American society, Capital, State, Empire undertakes a materialist critique of this digital society and assesses the impact of The New American Way of War, understood here as an outcome of a capitalist state's military budgets priorities under imperial strategy.